The contribution of local wisdom of the Baduy community to nature conservation: An ethnographic study based on ecological and customary perspectives - Permana, Sidik (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This study analyzes the cultural relations of the Baduy community in their efforts to conserve nature using a qualitative approach based on ethnography. Methods: Data was collected through non-participatory observation and unstructured interviews with nine informants from the Baduy indigenous community in Banten. The analysis uses social ecology theory and customary law. Findings: The results show that the Baduy community consistently practices norms, spirituality, and nature conservation that have been passed down by their ancestors, even as globalization and modernism sweep through. The findings show that the Baduy community possesses ecological wisdom that functions as a form of local environmental governance, integrating spiritual values with environmental ethics. Their resistance to modernization and industrialization is not a rejection of progress, but a conscious effort to maintain the balance between humans and nature in accordance with traditional values. Conclusion: This research, grounded in local wisdom, not only deepens readers' understanding of the Baduy indigenous community's role in preserving cultural identity while conserving nature but also aids in the design of government policies. Novelty/Originality of this article: This research expands on previous studies by highlighting the spiritual aspect of the Baduy indigenous community as an important ecological actor that has received little attention in studies of indigenous ecology.